Pyramiding rpg4- and Rpg1-Mediated Stem Rust Resistance in Barley Requires the Rrr1 Gene for Both to Function - Sharma Poudel, Roshan; Al-Hashel, Abdullah F.; Gross, Thomas; Gross, Patrick; Brueggeman, Robert (Frontiers in Plant Science, 2018)
Stem rust, caused by Puccinia graminis f. sp. tritici (Pgt) is an economically important disease of wheat and barley. Rpg1 is the only resistance gene deployed in Midwestern US barley varieties and provides remarkable resistance to most North American races, except Pgt race QCCJB. Rpg1 is also ineffective against Pgt race TTKSK and its lineage that originated in Africa. The barley rpg4-mediated resistance locus (RMRL) conferring resistance to Pgt races QCCJB and TTKSK was isolated from line Q21861, which is resistant to all known Pgt races due to Rpg1 and RMRL. To develop elite barley varieties RMRL was pyramided into the varieties, Pinnacle and Conlon (both contain Rpg1), producing the near isogenic lines (NILs), Pinnacle RMRL-NIL (PRN) and Conlon RMRL-NIL (CRN). The CRN was resistant to Pgt races QCCJB (RMRL specific) and HKHJC (Rpg1 specific) at the seedling stage and Pgt race TTKSK (RMRL specific) at the adult stage. In contrast, PRN was susceptible to QCCJB and HKHJC at the seedling stage and TTKSK at the adult stage. Interestingly, PRN’s susceptibility to QCCJB and HKHJC showed that RMRL was non functional in the Pinnacle background but its presence also suppressed Rpg1-mediated resistance. Thus, in the absence of a gene/s found in the Q21861 background, Rpg1 becomes non functional if RMRL is present, suggesting that another polymorphic gene, that we designated Rrr1 (required for rpg4-mediated resistance 1), is required for RMRL resistance and Rpg1-mediated resistance in the presence of RMRL. Utilizing a PRN/Q21861 derived recombinant inbred line (RIL) population, Rrr1 was delimited to a ~0.5MB physical region, slightly proximal (~1.8MB) of RMRL on barley chromosome 5H. A second gene, designated required for Rpg1-mediated resistance 2 (Rrr2), with duplicate gene action to Rrr1 in Rpg1-mediated resistance function, was genetically delimited to a physical region of ~0.7MB, slightly distal (~3.1MB) to Rpg1 on the short arm of barley chromosome 7H. Thus, Rrr1 is required for RMRL resistance and Rrr1 or Rrr2 is required for functional Rpg1-mediated resistance in the presence of the RMRL introgression. Candidate Rrr1 and Rrr2 genes were identified that need to be considered when pyramiding Rpg1 and RMRL in barley.